2020
DOI: 10.4067/s0717-95022020000501330
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Corchorus olitorius and Protacatechuic Acid on Diabetic Rat Testis Tissue

Abstract: The aim of this study is to investigate the effects of Protocatechuic acid and Corchorus olitorius on streptozotocin (STZ) induced diabetic rat testis tissue. Randomly selected Wistar Albino rats were divided into five groups as; Diabetes Mellitus, Diabetes Mellitus treated with Corchorus Olitorus (STZ+CO), Diabetes Mellitus treated with Protacatechuic acid (STZ+PCA), Corchorus olitorius (CO), Protocatechuic acid (PCA) and Control. Diabetic model was generated by intraperitoneal injection of 60 mg/kg Streptozo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 19 publications
(17 reference statements)
0
2
0
Order By: Relevance
“…For example, Anyasor et al ( 50 ) demonstrated that using 80 g ethanolic extract of C. olitorius leaf for 13 days in T2D rats could improve glucose metabolism, as revealed by a significant decrease in plasma glucose in the treated group (99.0 mg/dL) compared to 313.5 mg/dL, p < 0.05 in the control group. Similarly, Mercan et al ( 52 ) reported that the administration of 96% ethanolic extract of C. olitorius (250 mg/kg) for 3 weeks in STZ-induced T2D Wistar albino rats could significantly decrease FBG (297.83 mg/dL) when compared to untreated STZ rats (419.00 mg/dL, p < 0.05). The same study revealed a 0.44-fold decrease in FBG when baseline and post-treatment results were compared.…”
Section: Effect Of C Olitorius On the Body Weight ...mentioning
confidence: 81%
“…For example, Anyasor et al ( 50 ) demonstrated that using 80 g ethanolic extract of C. olitorius leaf for 13 days in T2D rats could improve glucose metabolism, as revealed by a significant decrease in plasma glucose in the treated group (99.0 mg/dL) compared to 313.5 mg/dL, p < 0.05 in the control group. Similarly, Mercan et al ( 52 ) reported that the administration of 96% ethanolic extract of C. olitorius (250 mg/kg) for 3 weeks in STZ-induced T2D Wistar albino rats could significantly decrease FBG (297.83 mg/dL) when compared to untreated STZ rats (419.00 mg/dL, p < 0.05). The same study revealed a 0.44-fold decrease in FBG when baseline and post-treatment results were compared.…”
Section: Effect Of C Olitorius On the Body Weight ...mentioning
confidence: 81%
“…A group of researchers studied the effect of C. olitorius in structural changes of testicular tissue in streptozotocin-induced diabetic rats [ 126 ]. They found that blood glucose levels significantly decreased in the treatment groups compared with the diabetic group; seminiferous tubule degenerations were prevented, and apoptotic cell numbers were reduced.…”
Section: Biological Activitymentioning
confidence: 99%